FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO PRODUKSI USAHATANI KANGKUNG DARAT DI DESA WARU KECAMATAN MRANGGEN KABUPATEN DEMAK - Diana Rarasati; Tinjung Mary Prihtanti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
Ground water spinach (Ipomea reptana) is one type of horticultural commodity that can contribute to national development in order to realize community welfare, including for the fulfillment of nutrition for the community as a complement to four healthy five perfect foods, besides that ground water spinach can also be potential and prospective if made a business because cultivating ground water spinach is easy and simple. The purpose of this study is to analyze the factors that influence the risk of production of ground water spinach farming and this study was conducted in Waru Village, Mranggen District, Demak Regency. The sampling technique is by using quota sampling by taking a sample of 50 farmers, where this sample can meet the criteria of quota sampling. The quota sampling criteria used were respondents who conducted ground water spinach cultivation. The method of analysis uses production risk analysis with the Just and Pope model based on the Cobb-Douglas production function model, where Just and Pope is used to determine the effect of the use of production factors on production risk as indicated by variations in output productivity. The results of research that have been carried out that the factors of production that affect the risk of production of kangkung inland farming significantly affect the risk of production are seeds by 0.0569 with a coefficient of 0.0573.